ZmRAP2.7, an AP2 Transcription Factor, Is Involved in Maize Brace Roots Development - Li, Jieping; Chen, Fanjun; Li, Yanqing; Li, Pengcheng; Wang, Yuanqing; Mi, Guohua; Yuan, Lixing (Frontiers in Plant Science, 2019)
In maize shoot-borne roots dominate the whole root system and play essential roles in water and nutrient acquisition and lodging tolerance. Shoot-borne roots are initiated at shoot nodes, including crown roots from the belowground nodes and brace roots from aboveground nodes. In contrast to crown roots, few genes for brace roots development have been identified. Here, we characterized a maize AP2/ERF transcriptional factor, ZmRAP2.7, to be involved in brace root development. ZmRAP2.7 expressed in all types of roots, and the encoded protein localized in the nuclear with transcriptional activation activity. A maize transposon target mutant RAP2.7-Mu defective in ZmRAP2.7 expression revealed a decreased number of brace roots but not crown roots. Maize Corngrass1 mutant which showed an elevated expression of ZmRAP2.7, however, revealed an increased number of brace roots. The ZmRAP2.7-based association analysis in a maize panel further identified a SNP marker at the fifth exon of gene to be associated with number of brace roots. These results uncovered a function of ZmRAP2.7 in brace root development, and provided the valuable gene and allele for genetic improvement of maize root systems.